Assessing the Impact of Requests for Information in Electrical and Instrumentation Engineering Contracts - Love, Peter; Zhou, Jingyang; Sing, Michael; Kim, J. (Taylor & Francis, 2014)
Using a case study, errors, omissions and information redundancy contained in the electrical and instrumentation (E&I) ‘As-built’drawings for a Stacker Conveyor were examined.Atotal of 449 errors and omissions were identified within 42 documents. In addition, 231 cables and components appeared once among the 42 documents; 86 cables and components appeared twice and 12 cables and components appeared thrice. As a result of the errors, omissions and redundancy, requests for information (RFIs) were required. Retrospective analysis indicates that the indirect cost of raising the RFIs to the contractor was estimated to be approximately 9% of the cost of the E&I contract. To address the problems of errors, omissions and redundancy, it is suggested that there is a need to adopt an object orientated system information model (SIM) for E&I engineering design and documentation. It is demonstrated in the case study that the use of a SIM could bring significant improvements in productivity and reduce the cost of engineering design.